The future of food tourism foodies, experiences, exclusivity, visions and political capital - Yeoman, Ian (Aspects of tourism, 2015)
This book presents a systematic and pattern-based explanation of food tourism, focusing on how and why change could occur and what the implications could be. In the future will food tourism involve food grown in the laboratory or a more authentic experience? The book explores these and many other futures and scenarios.